Red Breasted Goose - Museum Specimen - Campbell, Sandy (2018)
The red-breasted goose breeds in Arctic Siberia. This specimen is on display in the Polar collection at the Swedish Royal Museum of Natural History (Naturhistoriska riksmuseet) in Stockholm.